(untitled) (Eurasian Journal of Research, Development and Innovation, 2025)
The article analyzes the importance of students’ economic and legal knowledge and the key to a prosperous life without corruption. This article explains the importance of developing fair relations, anti-corruption skills and a sense of social responsibility in students through the formation of an economic and legal culture. The main points presented in the article provide information on the role that students, having acquired an economic and legal culture, play in ensuring a prosperous life and maintaining social stability. This process will also be important in strengthening mutual trust and cooperation in society and solving complex social problems.